TIBIA DIAPHYSEAL FRACTURE - Jeremić, Danilo; Tomić, Slavko (Medicinski podmladak, 2023)
Fractures of the tibial diaphysis are common fractures of long bones. Open fractures are frequent in tibial fractures, often associated with severe injuries to bones and soft tissues. Treatment begins with a careful assessment of the patient and tibial injury. The pathophysiology of tibial fractures may vary depending on the mechanism of injury. Injuries can be caused by direct and indirect force. Sports, traffic accidents, and falls are common causes of these injuries. Open fractures are more common in men and often require urgent treatment. Classification of fractures is used to assess the severity of the injury. There are different classifications, such as the Gustilo-Anderson classification for open fractures and the Tscherne and Gotzen classification for closed fractures. Treatment can be non-operative or operative, depending on the degree of displacement and the condition of the soft tissues. Complications of tibial fractures include nonunion, malunion, infections, circulatory disturbances, and compartment syndrome. Accurate diagnosis and appropriate treatment are essential for achieving favorable outcomes and reducing complications in tibial diaphysis fractures. Patients usually show improved function over several months after the injury, but some may experience pain and the development of posttraumatic arthritis in the long term. Therefore, a careful approach to assessing and treating patients with tibial fractures is necessary.